Detection of feline coronavirus in cerebrospinal fluid for diagnosis of feline infectious peritonitis in cats with and without neurological signs. Issue 2 (February 2016) - Doenges, Stephanie J; Weber, Karin; Dorsch, Roswitha; Fux, Robert; Fischer, Andrea; Matiasek, Lara A; Matiasek, Kaspar; Hartmann, Katrin
Objectives: The objective of this study was to evaluate the sensitivity and specificity of a real-time reverse transcriptase polymerase chain reaction (real-time RT-PCR) detecting feline coronavirus (FCoV) RNA in cerebrospinal fluid (CSF) of cats with and without neurological and/or ocular signs for the diagnosis of feline infectious peritonitis (FIP). Methods: This prospective case-control study included 34 cats. Nineteen cats had a definitive histopathological diagnosis of FIP (seven of these with neurological and/or ocular signs), and 15 cats had other diseases but similar clinical signs (three of these with neurological and/or ocular signs). Real-time RT-PCR was performed on the CSF of all cats, and sensitivity, specificity, and positive (PPV) and negative predictive values (NPV) were calculated. Results: Real-time RT-PCR of CSF showed a specificity of 100% in diagnosing FIP, a sensitivity of 42.1%, a PPV of 100% and an NPV of 57.7%. The sensitivity of the real-time RT-PCR of CSF in cats with neurological and/or ocular signs was 85.7%. Conclusions and relevance: Although it is known that RT-PCR can give false positive results, especially if performed using serum or plasma, this real-time RT-PCR detecting FCoV RNA in CSF can be considered a reliable specific tool for the diagnosis of FIP. If only cats with neurological involvement are evaluated, the sensitivity of this real-time RT-PCR in CSF is also high.